2018
DOI: 10.1155/2018/8191526
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Dynamic Characteristic Analysis of a Landing String in Deepwater Riserless Drilling

Abstract: The landing string is an important component of deepwater riserless drilling systems. Determination of the dynamic characteristics of the landing string plays an essential role in its design for ensuring its safe operation. In this paper, a dynamic model is developed to investigate the dynamic response characteristics of a landing string, where a landing string in a marine environment is modeled as a flexible slender tube undergoing coupled transverse and axial motions. The heaving motion of the drilling platf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…When the structural composition of the mechanical transmission system changes, the modeling and solution need to be reconstructed, and the efficiency is not high. In response to this problem, Li [3] , Wang et al [4,5] , Liu and Wang [6,7] , Xu [8] , and Wang et al [9] proposed rapid dynamic analysis methods for specific systems, but the scope of application is limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the structural composition of the mechanical transmission system changes, the modeling and solution need to be reconstructed, and the efficiency is not high. In response to this problem, Li [3] , Wang et al [4,5] , Liu and Wang [6,7] , Xu [8] , and Wang et al [9] proposed rapid dynamic analysis methods for specific systems, but the scope of application is limited.…”
Section: Introductionmentioning
confidence: 99%
“…If the current mechanism unit is connected to N successor mechanism units through one common component k, the equivalent moment of force๐‘€ , the equivalent moment of inertia ๐ฝ or the equivalent force ๐น and equivalent mass ๐‘š of each successor mechanism unit on the common component can be obtained by Formula (4) or Formula ( 5), where: 1 ๐‘– ๐‘ . The equivalent moment of force ๐‘€ , the equivalent moment of inertia ๐ฝ or the equivalent force ๐น and the equivalent mass ๐‘š of the common component k which is finally equivalent to N subsequent mechanism units can be calculated by Formula (6).…”
mentioning
confidence: 99%
“…The results show that the platform motion, shear flow velocity and drill bit motion have significant effects on the axial force of the pipe string. The larger the platform motion amplitude or the higher the rig speed, the larger the maximum dynamic axial force, and the higher the shear flow velocity, the smaller the maximum dynamic axial force [6]. Liu et al analyzed the overall stress of drill pipe and shallow casing in riserless drilling and established the overall static model of pipe string and wellhead and the dynamic model of drill pipe.…”
Section: Introductionmentioning
confidence: 99%
“…However, the above models mainly focus on the vibration in a single direction, which can effectively predict the vibration of tubular structure with small aspect ratio, and its calculation accuracy decreased to predict the vibration of tubular structure with large aspect ratio. Also, some scholars [32][33][34] have found that the longitudinal/lateral coupling effects of tubular structure with large aspect ratio cannot be ignored. Therefore, in our recent work [21,22], the longitudinal/lateral coupling model of marine risers with consideration of the coupling effects of the CF and IL vibration were established.…”
Section: Introductionmentioning
confidence: 99%